2007
DOI: 10.1089/cbr.2007.304
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Dosimetry in GATE: Dose-Point Kernel Validation with GEANT4 4.8.1

Abstract: GATE is a recent Monte Carlo code, based on GEANT4, and used in nuclear medicine mainly for imaging and detector design. Our goal was to implement dosimetry within GATE (i.e., combining the excellent potential of Gate for image modeling with GEANT4 dosimetric capabilities. The latest release of GEANT4 (4.8.1) completely revised the electron multiple scattering propagation algorithm. In this work, we calculated dose point kernels (DPK) for 0.01, 0.05, 0.1, 1, and 3 MeV monoenergetic electrons. We then compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Because of the long calculation times required to compute an absorbed dose within an entire whole-body phantom at a spatial resolution of a few millimeters, modifications were made to reduce computational times to reasonable values. More recently, this group has been investigating use of the GATE Monte Carlo code which is based on the GEANT4 Monte Carlo software libraries developed at CERN, the high energy physics center in Geneva, Switzerland (27, 28). …”
Section: Overview Of Imaging-based Dosimetry Methodsmentioning
confidence: 99%
“…Because of the long calculation times required to compute an absorbed dose within an entire whole-body phantom at a spatial resolution of a few millimeters, modifications were made to reduce computational times to reasonable values. More recently, this group has been investigating use of the GATE Monte Carlo code which is based on the GEANT4 Monte Carlo software libraries developed at CERN, the high energy physics center in Geneva, Switzerland (27, 28). …”
Section: Overview Of Imaging-based Dosimetry Methodsmentioning
confidence: 99%
“…Ferrer et al found a nonstatistically significant difference when comparing GEANT4.8.1 to both ETRAN and MCNPX v2.5.0 at electron energies up to 1 MeV, except for 10 keV. 9 Conversely, the difference between MCNPX v2.5.0 and ETRAN was not statistically significant even for 10 keV electrons. This is in accordance with the fact that MCNPX v.2.5.0 uses essentially the same simulation algorithm as ETRAN. As regard bone, the comparison between FLUKA and PENEL-OPE yields higher differences than in water above 50 keV, with discrepancy up to 31% with 100 keV electrons and lower differences at the lower energies, 10 and 20 keV.…”
Section: Iva Monoenergetic Electronsmentioning
confidence: 97%
“…Water DPKs calculated with different codes have in fact been published over the years, starting from ETRAN kernels first reported in 1973 2 and then revised in 1991. 3 Subsequently, the data have been published with EGS4,4 ACCEPT, 5,6 and more recently with EGSnrc, 7 NOREC, 8 GEANT4, 9 MCNPX v.2.5.0, and PENELOPE v.2006. 10 Some of these publications have been considered in this study.…”
Section: Introductionmentioning
confidence: 99%
“…GATE is a well validated Monte Carlo simulation toolkit for SPECT, PET, CT and recently Radiotherapy (RT) applications, based on the Geant4 core, 17 whose applications include high energy, nuclear and accelerator physics, as well as studies in medical and space science. 18,19 An older version of GATE based on Geant4 4.8.1 was validated by Ferrer et al 20 by comparison of ETRAN and MCNPX codes. GATE v6.0, which makes use of the Geant4.9.2 Electromagnetic Physics Package, has already been validated for electron transport, generating electron DPKs and pencil beam kernels for an energy range between 15 keV and 20 MeV by Maigne et al 13 This release of GATE introduces a large number of modifications to the electron transport algorithms.…”
Section: Introductionmentioning
confidence: 99%